(untitled) (Journal of Hama University, 2024)
: This research aims to investigate the efficiency of different techniques for caries removal (conventional stainless steel Burs- Smart Burs II - Chemomechanical Technique - dental laser) and their effect on the micro hardness of Residual Dentin. The study included a caries removal of (40) human molars with occlusal caries. The sample was divided randomly into four equal groups: In the first group,the caries was removed by conventional method, in the second group the caries was removed by Smart Burs II, While the third and fourth groups the caries was removed by Chemomechanical Technique and ER:YAG Laser respectively. After completing the removal of dental caries, the samples was subjected to the surface microhardness test and the Vickers number was calculated using the (Galileo durometria) device. The micro hardness of residual dentinal surface after caries removal by ER:YAG laser was the highest compared to the rest of the caries removal techniques, however, there were no statistically significant differences between the two groups of caries removal by using laser and the conventional technique, while there were Significance differences between the two groups of caries removal using dental laser and conventional technique and the other two groups. This laboratory experiment showed the efficiency of the dental laser in the context of the process of dental caries removal, as well as the conventional technique